Cerebellar involvement in essential tremor with and without resting tremor: A Diffusion Tensor Imaging study. (June 2016) - Novellino, Fabiana; Nicoletti, Giuseppe; Cherubini, Andrea; Caligiuri, Maria Eugenia; Nisticò, Rita; Salsone, Maria; Morelli, Maurizio; Arabia, Gennarina; Cavalli, Salvatore Maria; Vaccaro, Maria Grazia; Chiriaco, Carmelina; Quattrone, Aldo
Abstract: Objective: Essential Tremor with resting tremor (rET) is a debated and poorly understood clinical phenotype. Converging evidences show that neurodegeneration of the cerebellum underlies the pathophysiology of ET, but it is not known if cerebellar changes also occurs in patients with rET. The aim of our study was to evaluate cerebellar microstructure in patients with ET with- (rET) and without resting tremor (ETwr) in comparison to healthy controls by MR Diffusion Tensor Imaging (DTI). Methods: We studied 67 patients with ET (rET: 29 and ETwr: 38) and 39 age-matched healthy controls (HC). DTI was performed to measure fractional anisotropy (FA) and mean diffusivity (MD) of white and grey matter (WM, GM) in the entire cerebellum and in right and left cerebellar hemispheres. Results: MD was significantly higher in the cerebellar GM of ET total group (10.39 ± 0.87) in comparison with HC (9.90 ± 0.71) (p = 0.0027). Interestingly, MD was significantly different when ETwr (10.48 ± 0.77) were compared with HC (p = 0.0017), whereas a trend toward significance were found between rET (10.29 ± 0.99) and HC (p = 0.067). No differences among groups were found in MD of cerebellar WM and in FA values neither in the WM nor in the GM. Conclusion: Our results demonstrate the presence of microstructural changes in the cerebellum of patients with ET. It is noteworthy that rET showed intermediate values compared to HC and ETwr, suggesting that rET shares part of the pathophysiological mechanisms of ETwr, but cerebellar involvement seems do not fully account for rET. In addition to the cerebellar loops, other networks may play a role in rET pathophysiology. Highlights: We evaluated cerebellum in patients with ET with- (rET) and without rest tremor (ETwr) by using DTI. We found an increase of cerebellar grey matter MD values in ETwr compared to HC. rET group showed intermediate grey matter MD values compared to HC and ETwr. Cerebellum is a key structure in ETwr, but only partially explains rET pathophysiology. In addition to cerebellar loops, other networks may play a role in rET.